Challenges teachers face when teaching ELL students in a private school in Mount Lebanon - Zeitoun, Samar; ., Helenelabed (Advances in Social Sciences Research Journal, 2018)
The purpose of this study was to measure the impact of an intervention program on ELLs (English language learners), coming from diverse backgrounds with a non-English or limited English language> The study was carried out in a K-12 private school in Mount Lebanon. The sample was comprised of 3 EIP (English Intensive program) teachers, 2 ELLs of different upper elementary levels (5 & 6), and English supervisor or coordinator, EIP supervisor (the researcher), and the head of elementary 2nd cycle division. The research methodology employed action research-multi case study, and data was collected via 3 tools pre and post the intervention through a mixed method qualitative and quantitative design. These were: (1) Classroom Data Collection tools within 2 types of tools that are observation tools pre and post implementation of workshops done to check the success of implementing new strategies with ELLs, and content analysis tool for students’ writing samples, pre and post implementation, to check the impact of the intervention program on enhancing their writing skills ;(2) Questionnaires: English Teachers’ Questionnaire for needs analysis, EIP teachers’ questionnaire to check the impact of the intervention program on teachers as a post implementation tool, and students’ questionnaire post implementation to check the impact of the intervention program on students; (3)Teachers’ interview pre implementation to measure supervisor’s practices, difficulties ELLs face, and teachers’ challenges in teaching ELLs , and to take further suggestions. Also, a post implementation interview was conducted to check effective strategies used to enhance writing skills of ELLs. Descriptive statistics and content analysis were used to analyze respectively qualitative and qualitative data. Results also pinpoints important activities that match unique ELLs’ needs and enhance their writing skills. The study ended by recommendations for educational supervisors and teachers